การพัฒนาตัวบ่งชี้รวมของคุณภาพการสอนในระดับอุดมศึกษา - รุ้งรังษี วิบูลชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
This study aims at analyzing the teaching process in higher education, developing composite indicators of the teaching quality in higher education, testing the measurement of the validity of the structural model of the quality of teaching in higher education with empirical data, and constructing a factor scale for the composite indicators of the teaching quality in higher education. The research consisted of two phases. The first step consisted of the analysis of the teaching process in higher education by carrying out content analysis from the document and interviews with specialists in higher education teaching so as to find the variables related to the process of teaching in higher education in Thailand and overseas. The second phase consisted of the development of composite indicators and constructing a factor scale for the composite indicators of the teaching quality in higher education. The subjects consisted of 1,464 teachers in state-run universities chosen by multistage random sampling. The data was gathered by using questionnaires and data analysis by exploratory factor analysis to group the variables and carry out a confirmatory factor analysis to test the validity of the structural model of the teaching quality in higher education. The results of the research showed that variables related to the teaching process in higher education consisted of teachers qualifications - - whether they are knowledgeable about teaching methodology and the content, and have faith in the teaching profession and learner variables -- whether they are responsible for their learning. As for the source of data, it had to be diverse and up-to-date. The teaching process variables consisted of teaching plans, different and various teaching styles, and various methods of evaluation. Product variables regarded the fact that learners are able to search for new data and knowledge, have problem-solving skills, as well as analytical and management skills. The composite indicators of the teaching quality in higher education consisted of 12 composite indicators in the order of factor loading, from high to low, namely placing importance on learners to develop the teaching and learning, supporting proactive learners, accepting the capability and different learning styles of learners, using skills in evaluating learners results, encouraging learners to express their opinions, using time and content of subject appropriately, being skilful in stimulating learners, preparing the readiness of learners and teachers well, encouraging good interactions with learners, focusing on the importance of the learning process and iearning time, preparing lesson plans, and being knowledgeable about the subject content, respectively. The 12 composite indicators of the teaching quality in higher education can be used to co-explain the quality of teaching. The results of the testing of the measurement of validity of the structural model of the teaching quality in higher education found that the model is consistent with the empirical data, with a Chi-Square = 2347.19, Goodness of Fit Index (GFI) = .94. When a confirmatory factor analysis was done for each field of study, it was found that each field of study has placed importance on the 12 composite indicators differently.